2012
DOI: 10.1051/0004-6361/201117979
|View full text |Cite
|
Sign up to set email alerts
|

Spatial damping of propagating kink waves due to mode coupling

Abstract: Aims. We investigate the damping process for propagating transverse velocity oscillations, observed to be ubiquitous in the solar corona, due to mode coupling. Methods. We perform 3D numerical simulations of footpoint-driven transverse waves propagating in a low β coronal plasma with a cylindrical density structure. Mode coupling in an inhomogeneous layer leads to the coupling of the kink mode to the Alfvén mode, observed as the decay of the transverse kink oscillations. Results. We consider the spatial dampin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 21 publications
10
109
2
Order By: Relevance
“…Hence the oscillation amplitude is described by a kind of Gaussian profile for small time and by the exponential function for larger time. This result is similar to one found by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012 for propagating waves. The dashed line in (30) we obtain t dc /Π = 4(π 2 κ) −1 .…”
Section: Examination Of Figs 1-3 Reveals That the Solution Can Be Wrsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence the oscillation amplitude is described by a kind of Gaussian profile for small time and by the exponential function for larger time. This result is similar to one found by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012 for propagating waves. The dashed line in (30) we obtain t dc /Π = 4(π 2 κ) −1 .…”
Section: Examination Of Figs 1-3 Reveals That the Solution Can Be Wrsupporting
confidence: 91%
“…In particular, it was shown with the use of connection formulae that in the linear approximation the waves damp exponentially with the distance from the driver, and the damping length has been calculated. The same problem has been studied numerically by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012. In particular, Pascoe et al (2012) have shown that the wave amplitude does not decay exponentially everywhere.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cross-correlation suggests the waves are propagating, implying an that initial increase in amplitude could be due to decreasing density with height. We speculate that the reduction in amplitude with height could be explained by spatial damping, e.g., by invoking resonant absorption as a damping mechanism for the transverse waves Pascoe et al 2012). Verth et al (2010) showed that resonant absorption is compatible with the decrease in propagating wave amplitude along coronal loops observed in CoMP (Tomczyk & McIntosh 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Also, Reference 1 1 261 870 168 A02 2 265 300 72 3 316 500 174 4 277 400 204 5 272 849 162 6 435 600 258 7 143 200 166 8 423 800 406 9 185 200 192 10 396 400 Eq. (2) does not describe any transient behaviour in the damping (Pascoe et al 2012). Equation (2) shows that the resonant absorption time-scale scales linearly with period.…”
Section: Statistics Of Transverse Loop Oscillationsmentioning
confidence: 99%